Fraudulent Financial Statements at Sharia Banks - Uciati, Neni; Mukhibad, Hasan (Accounting Analysis Journal, 2019)
This study aims to analyze the determinants of fraudulent financial statements in the perspective of crowe’s fraud pentagon theory at Sharia Commercial Banks in Indonesia. The population of this study was Sharia Commercial Banks in Indonesia with observation period in 2015-2018. Samples are selected by using purposive sampling method. Analysis of research data used panel data regression analysis. The results of this study indicate that sharia compliance, change in director and frequent number of CEO's picture have a positive and significant effect on fraudulent financial statements. This study also finds that financial stability, financial target, and effective monitoring have no significant effect on fraudulent financial statements. Sharia Commercial Banks are advised not to make changes to the composition of the board of directors within a short span of time so that financial fraud can be minimized. The weakness of this research is that there is a pressure condition in the element of the crowe’s fraud pentagon theory that has not been studied. The addition of research objects from several different countries as well as extending the period of observation is also recommended in order to obtain more accurate research results.